Country-of-Origin Effect on Domestic Product Evaluation and Purchase Intention Relationship in India - Jain, Reetika (Prabandhan: Indian Journal of Management, 2023)
Globalization has paved the way to diminishing boundaries and increasing trade between countries. Consumers today have vast choices of products originating in both domestic boundaries as well as foreign countries. Yet, all foreign products are not viewed with the same pride and esteem. Products originating from different countries have different perceptions in the minds of consumers. The COO research has gained further importance in the current COVID-19 pandemic scenario, given the Government of Indiaâ€™s wide-scale initiatives towards Atmanirbhar Bharat to make India more self-reliant, and the people of India are widely accepting such views. Few researchers have studied the COO effect on purchase preference for domestic vis-Ã -vis foreign products in India. The present study, therefore, investigated the country-of-origin effect on the relationship between the evaluation of domestic products and their purchase intention in the Indian context. The COO effect was investigated for the home country as well as a foreign country, that is, China. Understanding the country-of-origin effect of imported products vis-Ã -vis domestic products helps marketers plan their marketing strategies at both domestic and international levels.